1978
DOI: 10.1136/sti.54.5.350
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the penis developed in lichen sclerosus et atrophicus.

Abstract: SUMMARY Malignant change developing in lichen sclerosus et atrophicus is rare in men. A case is described in a 39-year-old man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Zoon's balanitis is not associated with malignancy, however Joshi has recently reported a case of squamous 574 International Journal of STD & AIDS Volume 13 August 2002 Lichen sclerosus is associated with destructive in¯ammation, phimosis, urethral stenosis and squamous cell carcinoma 10 . There have been many case reports showing the association between lichen sclerosus and squamous cell carcinoma of penis 11,12,13 . In one study of patients with penile lichen sclerosus with long term follow-up Micali et al reported 9.3% of patients with lichen sclerosus developed an epithelial cancer 14 .…”
Section: Discussionmentioning
confidence: 98%
“…Zoon's balanitis is not associated with malignancy, however Joshi has recently reported a case of squamous 574 International Journal of STD & AIDS Volume 13 August 2002 Lichen sclerosus is associated with destructive in¯ammation, phimosis, urethral stenosis and squamous cell carcinoma 10 . There have been many case reports showing the association between lichen sclerosus and squamous cell carcinoma of penis 11,12,13 . In one study of patients with penile lichen sclerosus with long term follow-up Micali et al reported 9.3% of patients with lichen sclerosus developed an epithelial cancer 14 .…”
Section: Discussionmentioning
confidence: 98%
“…For penile SCC that has followed LSA, most cases represent squamous cell carcinoma (21)(22)(23)(24), but also case reports of verrucous carcinoma (18) and adenosquamous carcinoma (25) exist. A 10-year follow-up study of 86 men with LSA found that 6% of the patients developed penile cancer, implying that LSA is, in analogy to vulvar cancer, also a major risk factor for penile cancer (26).…”
Section: Lichen Sclerosus Et Atrophicus (Lsa)mentioning
confidence: 99%
“…Development of squamous cell carcinoma has been reported in patients with balanitis xerotica obliterans, both in areas of active and quiescent disease,64 65 but malignant change appears to be less common than in lichen sclerosus et atrophicus in the female.65…”
Section: Spirochaetal Infectionmentioning
confidence: 99%